The profile of the overdose patient admitted to a tertiary hospital in Gauteng - Gihwala, Radha (My University, 2016)
Background Overdose is an important health care problem, a subject under-researched in South Africa. The aims of this study are to investigate the demographics, to identify common substances and to ascertain the burden of disease at a tertiary hospital in Gauteng. Data can be used to reduce morbidity, mortality and the substantial costs to health care services related to overdose. Materials and methods A retrospective, observational study based on hospital records (16 weeks). The analysis was purely descriptive. Categorical data were compared using the Chisquare test. P value < 0.05 was considered significant. Results Of the total of 176 records with a primary diagnosis of overdose, 133 were included. The frequency of overdose was found to be 1.1 cases per day. Females accounted for 64.7%, 82.8% were single, 85% were Black, 78.9% were unemployed and 54.2% resided in poor socio-economic areas. Overdose was highest in the 20-29 years (55.6%) age group with a mean age of 28.1 years. Overdose was intentional in 91% and 12% of the subjects had overdosed previously. A previous medical history was found in 22.6% and HIV was prevalent in 66.7%. The most common substance groups were analgesics (32.3%), pesticides (21.1%), anxiolytics (11.3%), household chemicals (10.5%), vitamins (8.3%), antibiotics (7.5%) and anti-retrovirals (ARV’s) (5.3%). In 99.3% the substance was ingested orally and in 23.3% there was concurrent alcohol consumption. Common precipitating factors were relationship problems, depression, domestic problems and financial. The median delay to hospital presentation was 3.5 hours and patients tended to present during the afternoon and the night with a significant association between time of presentation and age group (p=0.043). An antidote was employed in 35.3% and in 97% of cases, symptomatic treatment was by far the most common. No patients were discharged directly from the ED and in 42.1% the median length of hospital stay was 2 days and a case fatality rate of 1.5%. Conclusion The introduction of management protocols is of uttermost importance. Awareness, education and regulations will form part of strategies for the prevention of overdose.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Medicine in Emergency Medicine. Johannesburg, 2016
Keywords: Overdose